Distributed processing of color and form in the visual cortex - Rentzeperis, Ilias; Nikolaev, Andrey R.; Kiper, Daniel C.; van Leeuwen, Cees (Frontiers in Psychology, 2014)
To what extent does the visual system process color and form separately? Proponents of the segregation view claim that distinct regions of the cortex are dedicated to each of these two dimensions separately. However, evidence is accumulating that color and form processing may, at least to some extent, be intertwined in the brain. In this perspective, we review psychophysical and neurophysiological studies on color and form perception and evaluate their results in light of recent developments in population coding.